Мэргэжлийн англи хэлний хөтөлбөрийн харьцуулсан судалгаа: Some comparison of english for specific purposes curriculum - S., Chimedtsogzol (Mongolian Journal of Foreign Languages and Cultures, 2023)
From the early 1960’s, English for Specific Purposes (ESP) has grown to become one of the most prominent areas of EFL teaching today. ESP concentrates more on language in context than on teaching grammar and language structures. It covers subjects varying from accounting, business management, law, biology, geology, history, and chemistry. The ESP focal point is that English is not taught as a subject separated from the students’ real world (or wishes); instead, it is integrated into a subject matter area important to the learners.